1999
DOI: 10.1128/aac.43.6.1412
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled, Double-Blind Trial To Evaluate the Efficacy of Mupirocin for Eradicating Carriage of Methicillin-Resistant Staphylococcus aureus

Abstract: Mupirocin has been widely used for the clearance of nasal methicillin-resistant Staphylococcus aureus (MRSA) carriage during outbreaks, but no placebo-controlled trial has evaluated its value for eradicating MRSA carriage at multiple body sites in settings where MRSA is not epidemic. In a 1,500-bed teaching hospital with endemic MRSA, 102 patients colonized with MRSA were randomized into a double-blind, placebo-controlled trial and treated with either mupirocin (group M) or placebo (group P) applied to the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
2
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(152 citation statements)
references
References 37 publications
6
134
2
9
Order By: Relevance
“…Our results are in contrast to the prospective studies of Sloot et al [7] and Rohr et al [8], who achieved eradication in 75% (28 patients, washing once daily for 5 days) and 64%, respectively (32 patients, washing once daily for 5 days), of patients with whole body washing with octenidine and mupirocin nasal ointment. In an earlier study [6], 14 persons (100%) were cleared of MRSA by washing with triclosan three times a day with eradication after an average of 22 days. Wenisch et al [11] demonstrated MRSA eradication in 100% of evaluable patients with pneumonia caused by MRSA by a holistic approach comprising of intravenous linezolid and rifampicin plus intratracheal vancomycin plus intranasal mupirocin plus skin and oropharyngeal washings with chlorhexidine plus wound treatment with polyvidone-iodide.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results are in contrast to the prospective studies of Sloot et al [7] and Rohr et al [8], who achieved eradication in 75% (28 patients, washing once daily for 5 days) and 64%, respectively (32 patients, washing once daily for 5 days), of patients with whole body washing with octenidine and mupirocin nasal ointment. In an earlier study [6], 14 persons (100%) were cleared of MRSA by washing with triclosan three times a day with eradication after an average of 22 days. Wenisch et al [11] demonstrated MRSA eradication in 100% of evaluable patients with pneumonia caused by MRSA by a holistic approach comprising of intravenous linezolid and rifampicin plus intratracheal vancomycin plus intranasal mupirocin plus skin and oropharyngeal washings with chlorhexidine plus wound treatment with polyvidone-iodide.…”
Section: Discussionmentioning
confidence: 98%
“…Harbarth et al [6] found that mupirocin was only marginally effective in the eradication of multisite MRSA carriage in a setting where MRSA was not epidemic. In their study MRSA was eradicated by antiseptic washings with chlorhexidine and mupirocin nasal ointment in 25% of patients only.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mupirocin 2% nasal ointment administered for 5 days has been shown to be an effective agent for the elimination of S. aureus carriage [50]. In a randomized controlled trial, treatment with topical mupirocin, chlorhexidine gluconate washes, oral rifampin, and doxycycline for 7 days was safe and effective in eradicating MRSA colonization in hospitalized patients for at least 3 months [51].…”
Section: Infection Control and Preventionmentioning
confidence: 99%
“…MRSA colonization at two or more body sites has been associated with persistent colonization [9]. A study examining the efficacy of mupirocin for eliminating MRSA colonization among hospitalized patients in Switzerland found that at study enrollment, 58% of participants had nasal colonization, 46% had skin colonization (pressure sores or skin lacerations), 38% had groin colonization, 20% had urine colonization, and 70% of patients were colonized at more than one body site [10]. In another study, when stool specimens submitted for Clostridium difficile toxin analysis were examined, 9.8% of hospitalized patients were found to have MRSA in their stool [11].…”
Section: Introductionmentioning
confidence: 99%